Translation Analysis of Address Terms in the Novel Entitled Percy Jackson & The Olympians: The Lightning Thief - Isdhianty, Marita Dwi (Universitas Sebelas Maret, 2021)
The aims of this study are to identify the type of address terms found in an English novel entitled Percy Jackson & The Olympians: The lightning thief, to identify translation techniques used by the Indonesian translator to translate the address terms, and to describe translation quality of address terms in the novel entitled Percy Jackson & The Olympians: The lightning thief. It is a qualitative study of which data are words and phrases accommodating address terms in English as source text and it’s translation as target text. The data were collected through content analysis and focus group discussion. The collected data were then analyzed based on data analysis model which is proposed by Spradley. There are 15 types of address term found in the novel. The translator uses established equivalent to translate type of address terms in the novel, such as title, generic first name, mockery name, etc. She also uses pure borrowing to translate first name, diminutive name, last name, etc. The accuracy and the acceptability of the translation of the address terms are quite high. It is a result of the application of established equivalent technique and pure borrowing.